O slogan: Eficácia e persuasão em texto condensado - Barbosa, Miriam Bacha Miranda (2006)
This research aims to study the advertising slogan in its linguistic and communicative aspects in order to understand how and why it reaches the readers and remains in their memory making them easily identify the product that is being advertised. The slogan reminds us of an iceberg top, by the few words that comprise it, yet making it possible for the reader to retrieve a huge submerged universe, as it is the biggest part of that ice block. Cook (1992) says that what is not said in a discourse is what is the most important, because it reflects what people assume to be the truth and admit to be correct. This way, the role of the shared knowledge becomes particularly significant because many advertisements turn to intertextual references built from the writers /readers shared experiences. Cook (1992) says that current advertisements are less worried about listing the products objective properties than about connecting them with some other entity, effect, person, etc., in order to make it possible to fulfill the featureless product with the desired features. This relation between the fictional world characters and the addressee is based on the assumption that there is enough shared knowledge to establish a feeling of intimacy, trust and informality. Downing (2003) says that the advertising discourse, by means of linguistic choices and context features - important factors in the determination of specific relations between addresser and addressee - can create an illusory world in which made up necessities can be originated. In this way, Sperber & Wilson (1986) say that implicatures perform an important role in advertising language. They can be defined as contextual assumptions that the speaker/writer hopes the receiver fulfills. This study has analyzed slogans which, in their great majority (70% of the total), were awarded the Top of Mind 2005 because they were able to achieve a high level of recall by consumers. The methodology we used in this analysis was the Systemic Functional Linguistics, developed by Halliday (1994; 2004). The data analysis was done including the ideational and interpersonal metafunctions from Halliday (1994) and the enacted and projected roles from Thompson & Thetela (1995).